Getting To Work - Research topic "Labour Market, Employment and Urbanization in Viet Nam to 2020: Lessons from International Experiences" - Ian Coxhead; Diep Phan; Dinh Vu Trang Ngan; Kim N. B. Ninh; Ian Coxhead; Diep Phan; Dinh Vu Trang Ngan; Kim N. B. Ninh
This report was commissioned by the Development Strategy Institute (DSI) of the Ministry of Planning and Investment and UNDP. The report contains views of the consultant team and does not necessarily refl ect the offi cial views or positions of DSI or UNDP.